Teaching Medical Spanish to Improve Population Health: Evidence for Incorporating Language Education and Assessment in U.S. Medical Schools - Norma P?rez (Mary Ann Liebert, 2019)
Introduction: Language concordance between patients and physicians is an important factor in providing safe and effective health care, with Spanish as the predominant and fastest growing non-English language in the United Sates. However, despite increasing demand for medical Spanish education, valid concerns about inadvertently increasing provider use of limited Spanish with patients, lack of knowledge of best practice in education and assessment, and lack of institutional support still present barriers to medical Spanish education in medical schools. Methods: The authors conducted a narrative review of existing literature that evaluates the link between medical Spanish education of physicians and language concordance. Results: Medical Spanish educational efforts, although increasing, are not consistently linked to learner assessment. The literature to date supports that for medical Spanish education to improve patient outcomes, it should be linked to assessment methodology that demonstrates improvement in language concordance with Spanish-speaking patients, and should include safety measures to prevent inadvertent communication errors. The authors review data for published medical Spanish postcourse language assessment strategies and provide recommendations to ensure responsible and competent use of medical Spanish skills. Conclusion: The authors propose three structural elements that should be considered when incorporating or enhancing medical Spanish education in medical schools: institutional endorsement of the role of medical Spanish education within a national health disparities context; precourse proficiency testing to establish student starting level; and learner postcourse communications skills and limitations assessment to provide individualized recommendations and assure patient safety.